Training Status Modulates Perceptual Responses During Constant-Load Cycling at Maximal Metabolic Steady State - Rodrigo de Araujo Bonetti de Poli; Brynn Eric Alexander Lindstrom; Pablo Rafael Fleitas-Paniagua; Rafael de Almeida Azevedo; Alessandro Moura Zagatto; Juan Manuel Murias (Medicine & Science in Sports & Exercise, 2026)
Purpose: Although perceptual scales are widely used to prescribe endurance training, whether aerobic training status influences perceptual responses to heavy-intensity exercise remains unclear. Thus, this study investigated the effects of aerobic training status on perceptual responses during cycling performed at the maximal metabolic steady state (MMSS). Methods: Thirty-two participants (untrained, n = 18; trained, n =14) performed:1) step-ramp-step to determine maximal oxygen uptake (V̇O 2max ) and, 2) MMSS estimated intensity, followed by at least two 30 min constant workload rides to confirm the MMSS. The MMSS was defined as the highest exercise intensity at which oxygen uptake and blood lactate concentration were stable between the 15 th and 30 th min of exercise (change